2011
DOI: 10.1007/s12185-011-0822-y
|View full text |Cite
|
Sign up to set email alerts
|

High maximum standard uptake value (SUVmax) on PET scan is associated with shorter survival in patients with diffuse large B cell lymphoma

Abstract: FDG-PET scan plays an important role in response assessment in diffuse large B cell lymphoma (DLBCL). In this study, we evaluated the prognostic value of maximum standard uptake (SUVmax) on pretreatment PET scan in DLBCL. Among 169 patients with DLBCL newly diagnosed and treated with R-CHOP between 2003 and 2008, 110 patients who had undergone pretreatment PET scan in single institute using an identical protocol were reviewed and analyzed. SUVmax at the predominant lesion on PET scan and other patient characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 23 publications
(22 reference statements)
3
57
3
Order By: Relevance
“…Previous studies suggested the association between SUV max and tumor aggressiveness [21][22][23]. And recently, the fact that proliferation potential of tumor cells measured by Ki-67 stain positively correlated with SUV max has been reported [24][25][26][27][28]. However, the measurement of SUV max has confined to the detection of the most obvious metabolic activity of the tumor at single site, but not the overall tumor activity.…”
mentioning
confidence: 99%
“…Previous studies suggested the association between SUV max and tumor aggressiveness [21][22][23]. And recently, the fact that proliferation potential of tumor cells measured by Ki-67 stain positively correlated with SUV max has been reported [24][25][26][27][28]. However, the measurement of SUV max has confined to the detection of the most obvious metabolic activity of the tumor at single site, but not the overall tumor activity.…”
mentioning
confidence: 99%
“…In fact, PET has been used for diagnosis, staging, and determining the treatment response of malignancies. Many studies have addressed the usefulness of the SUVmax on 18 F-FDG PET as a parameter for predicting survival in several cancers [13][14][15]. Lisle et al reported that the SUVmax on 18 F-FDG PET was found to be a prognostic factor of OS at a cutoff value of 4.35 in 44 patients with synovial sarcoma [13].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET provides physiologic information that enables cancer to be diagnosed on the basis of altered glucose metabolism [12]. Many studies have reported that the SUVmax on 18 F-FDG PET is a good indicator of tumor aggressiveness and a valuable parameter for predicting survival in several cancers [13][14][15]. Metabolic tumor volume (MTV) is tumor cells measured volumetrically or quantitatively by 18 F-FDG PET/CT [16].…”
Section: Introductionmentioning
confidence: 99%
“…Chihara (44) and colleagues revealed that a high SUVmax value was a significant poor prognostic factor for both PFS and OS in DLBCL, independent of the IPI. We found that the SUVmax value of T/NK-cell lymphomas was lower than that of aggressive B-cell lymphomas, despite the higher metabolic activity.…”
Section: Discussionmentioning
confidence: 99%